Pengaruh Orientasi Fashion, Money Attitude dan Self-Esteem terhadap Perilaku Pembelian Kompulsif pada Remaja (Studi pada Konsumen Produk Telepon Selular di Surabaya) - Andjarwati, Anik Lestari; Kristiyanto, Damar (BISMA (Bisnis dan Manajemen), 2018)
The commons phenomenon currently found is changing mobile phones among teens. The number of stimuli often makes teenagers buy a mobile phone in several times Such a behavior is categorized as compulsive buying behavior. Some of the teens showed awareness of the fashion orientation that resulted in the increased intensity of them to pay attention and follow fashion trends. While the mobile phone is now included into the category of fashion products. On the other hand, people increasingly make sense of money is not based on nominal or exchange value but rather the symbolic value of money where the value can affect a person's behavior in buying products. The behavior that interpret of the symbolic value of money is called the attitude toward money (money Attitudes). Later, teenagers is an age where have the highest self-esteem needs, where they are always looking for something that can enhance their self-image and demonstrate their existence in the association. This study aims to discuss and analyze the influence of Fashion Orientation, Money Attitudes and Self-Esteem on Compulsive Buying Behavior in teenagers (Studies In Consumer Products Cellular Phone In Surabaya). This study is conclusive research. The population in this study were respondents aged 15-24 years who live in Surabaya and has alternated mobile phone at least 4 times in one year. Samples taken as many as 210 people with accidental sampling technique. Measuring instrument used by questionnaire, and data were analyzed by multiple linear regression. The results showed that the influence of Fashion Orientation, Money Attitudes and Self-Esteem on Compulsive Buying Behavior by 48.2%, while the remaining balance is 51.8% influenced by other variables outside of the study. Fashion Orientation variables are the dominant variables that influence the Compulsive Buying Behavior